(untitled) - Forbes, Robert James (New York, 1968)
Since the dawn of history, mas has used his toolmaking ability to gain control of his environment. During the past three hundred years, however, and especially in this century, technological growth has accelerated to the point of outstripping our power to direct it. Increasingly we run the danger of falling captive to our creations. Distinguished scholar and thinker R. J. Forbes examines this disturbing paradox and its vast ramifications in a searching study of man and the machine over the centuries, and the critical stage this shifting relationship has reached today. His book offers acutely penetrating insight into the promise and the peril of our age of automation, the computer and H-bomb.
Keywords: Technology and civilization,Công nghệ và văn minh